The use of large healthcare data sets in pursuit of a clinical question. Issue 5 (16th March 2015) - Arons, Raymond R.; Taub, Leslie‐Faith Morritt
Abstract The use of large healthcare databases may be of interest to nurse practitioners who wish to answer clinical questions. This column will provide information about access to selected large healthcare databases, requirements for statistical software, and the skills required to utilize these databases.